Derivation and Validation of an Optimal Neutrophil Gelatinase-Associated Lipocalin Cutoff to Predict Stage 2/3 Acute Kidney Injury (AKI) in Critically Ill Children - Stuart L. Goldstein; Ayse Akcan-Arikan; Natasha Afonso; David J. Askenazi; Abby M. Basalely; Rajit K. Basu; Hostensia Beng; Julie C. Fitzgerald; Katja Gist; Sarah Kizilbash; David Kwiatkowski; Christopher W. Mastropietro; et al. (Kidney International Reports)
Introduction: Acute kidney injury (AKI) defined by changes in serum creatinine (SCr), or oliguria is associated with increased morbidity and mortality in children who are critically ill. We derived and validated a clinical cutoff value for urine neutrophil gelatinase-associated lipocalin (NGAL), in a prospective multicenter study of children who were critically ill. We report the clinical performance of urine NGAL (uNGAL) to aid in pediatric AKI risk assessment. Methods: Eligible subjects were aged ≥ 90 days to < 22 years, admitted to an intensive care unit (ICU), and had 1 or more of the following: mechanical ventilation, vasoactive medication administration, solid organ or bone marrow transplantation, or hypotension within 24-hours of admission. uNGAL was assessed within 24-hours of admission. The primary outcome was SCr-based stage 2/3 AKI presence at 48- to 72-hours. Results: Twenty-five (12.3%) derivation study patients had stage 2/3 AKI at 48- to 72-hours. uNGAL concentration of 125 ng/ml was the optimal cutoff. Forty-seven (9.1%) validation study patients had stage 2/3 AKI at 48- to 72-hours. The area under the curve of a receiver operator characteristics curve (AUC-ROC) for uNGAL performance was 0.83 (95% confidence interval [CI]: 0.77–0.90). Performance characteristics were sensitivity 72.3% (95% CI: 57.4%–84.4%), specificity 86.3% (95% CI: 82.8%–89.3%), positive predictive value 34.7% (95% CI: 28.5%–41.5%), and negative predictive value 96.9% (95% CI: 95.1%–98.0%). Conclusion: These prospective, pediatric, multicenter studies demonstrate that uNGAL in the first 24-hours performs very well to predict Kidney Disease Improving Global Outcomes (KDIGO) stage 2/3 AKI at 48- to 72-hours into an ICU course. We suggest that a uNGAL cut point of 125 ng/ml can aid in the risk assessment for stage 2/3 AKI persistence or development.